The Long-Run Superneutrality of Money Revised: the Extended European Evidence - Oleg Deev; Martin Hodula (Review of Economic Perspectives, 2016)
This article investigates the validity of the money superneutrality concept for the large panel of European economies. While focusing exclusively on endogenous growth theories including the Mundell-Tobin effect, we examine the long-run response of real output to a permanent inflation shock in every studied country using a structural vector autoregressive framework. For the majority of countries in our sample, the longrun superneutrality concept is confirmed since the original increase/decrease in output growth fades in time. We also test the additional hypothesis of whether the group of countries with smaller in-sample inflation mean forms the exception to the long-run money superneutrality. As the result, modern economies might be better described from the viewpoint of Sidrauski.
Keywords: 330; endogenous growth theories; superneutrality; SVAR